1988
DOI: 10.1111/j.1432-1033.1988.tb13916.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic properties of colicin A

Abstract: The hydrodynamic properties of colicin A have been studied. The molecular mass of colicin A was determined from sedimentation equilibrium centrifugation to be 63 f 1.2 kDa, in agreement with that determined from the primary amino acid sequence [Morlon et al. (1983) J . Mol. Biol. 110, 271 -2891. The sedimentation coefficient has been analyzed over a wide range of ionic strength (NaCl 0.06-0.56 M) and pH and was found to remain almost constant. However, below pH 5 an oligomerization of colicin A to tetramers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Axial ratios ranging from 7 to 20 were found for colicins E2, E3, Ia, and Ib, with I colicins being more elongated (358). Further hydrodynamic analyses of colicin A have shown that it forms tetramers at acidic pHs and that while full-length colicin A is an asymmetric molecule, the isolated translocation domain is globular (102,345). The structure of the C-terminal domain of colicin A has been solved by X-ray crystallography, in part due to the emergent technique of sitedirected mutagenesis.…”
Section: Three-dimensional Structures Of Colicinsmentioning
confidence: 99%
“…Axial ratios ranging from 7 to 20 were found for colicins E2, E3, Ia, and Ib, with I colicins being more elongated (358). Further hydrodynamic analyses of colicin A have shown that it forms tetramers at acidic pHs and that while full-length colicin A is an asymmetric molecule, the isolated translocation domain is globular (102,345). The structure of the C-terminal domain of colicin A has been solved by X-ray crystallography, in part due to the emergent technique of sitedirected mutagenesis.…”
Section: Three-dimensional Structures Of Colicinsmentioning
confidence: 99%
“…The analytical centrifugation experiments indicated the oligomeric state of the proteins. TolAIII and TolAII were monomeric in solution (data not shown), as was colicin A (Cavard et al, 1988) and its N-terminal domain (Knibiehler et al, 1989).…”
Section: Estimation Of the Kinetic Values Of Colicin Binding To Immobmentioning
confidence: 99%
“…The intact colicin A was found to be highly asymetric [3] while the AT1 protein which accounts for about a third of the entire molecule is not asymetric with an axial ratio of about 2.4. In contrast, the 20-kDa C-terminal domain is highly structured [l, 2.…”
Section: Discussionmentioning
confidence: 99%
“…The AT1 protein also has little affinity for phospholipid monolayers, despite the fact that colicin A itself displays strong affinity for lipids [3,161. Colicin A derivatives which lack the N-terminal domain can both bind to receptors and form ion channels in vitro but cannot kill sensitive cells [I, 51. Since the N-terminal domain is required for transport of colicin A across the outer membrane, it is tempting to speculate that the role of this region of the colicin involves its interaction with cellular components which function to transport it to the inner membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation